Gabon : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2006)
Gabon partially complies with the principles of the Code of Good Practices on Fiscal Transparency and the Guide on Resource Revenue Transparency. Much remains to be done to ensure that government finances are managed transparently, in conformity with international best practices. Knowledge and dissemination of reliable and accurate fiscal information are essential. The budget must be prepared in such a way that the best short- and medium-term choices can be made in achieving the government's key objectives-development and poverty reduction.